Electricity Reform in Ukraine : The Impact of Weak Goverance and Budget Crises - Lovei, Laszlo (World Bank, Washington, DC, 2012)
Although reform of Ukraine's electricity sector is far from complete, the experience so far shows that ingrained attitudes are harder to change than written rules of the game. Moreover, the reemergence of old behavioral patterns during political, macroeconomic, or sectoral crises can quickly undermine early gains from reform. Thus the long time needed to achieve deep and irreversible changes places a high premium on stamina and patience for reformers. By contrast, and contrary to some predictions, in Ukraine it was relatively easy to put in place the basic systems for a functioning competitive electricity market. Dispatch center, generation, and distribution company employees quickly learned to work with the new procedures and demonstrated a remarkable ability to adapt imported solutions to local conditions.